2018
DOI: 10.1007/s10903-018-0727-4
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Type of Heart Failure and Hospitalization

Abstract: Heart failure (HF) is one of the leading causes of hospitalization and readmissions. Our study aimed to examine racial disparities in heart failure patients including onset, mortality, length of stay (LOS), direct costs, and readmission rates. This is a secondary data analysis. We analyzed the risk-adjusted inpatient data of all patients admitted with HF to one health academic center. We compared five health outcomes among three racial groups (white, black, and Hispanic). There were 1006 adult patients making … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…HF and renal disease, 20,24,30 and 4 studies reported results for HFrEF or HFpEF subgroups. 17,27,30,33 No studies included in this review reported on the cost per hospitalization for the subgroup of patient with both HF and diabetes. 2).…”
Section: Figure 1 Prisma Diagrammentioning
confidence: 99%
See 1 more Smart Citation
“…HF and renal disease, 20,24,30 and 4 studies reported results for HFrEF or HFpEF subgroups. 17,27,30,33 No studies included in this review reported on the cost per hospitalization for the subgroup of patient with both HF and diabetes. 2).…”
Section: Figure 1 Prisma Diagrammentioning
confidence: 99%
“…17,25 Among studies reporting the distribution of primary insurance payer type, Medicare was the most frequently reported primary payer. The percentage of patients with Medicare as the primary payer ranged from 58% to 100% 17,19,22,25 ; the percentage with primary commercial coverage ranged from 7% to 17% 18,27 ; the percentage with primary Medicaid coverage ranged from 8% to 12% 5,27,32 ; and the percentage with primary private coverage ranged from 3% to 23%. 17,18 Among the studies that reported on the percentage of individuals who had key HF-related comorbidities, the percentage of patients with diabetes ranged from 29.0% to 47.9%, 5,25 with kidney disease from 0.2% to 55.7%, 18,29 with cerebrovascular disease from 1.0% to 13.5%, 25,33 with obesity from 14.3% to 21.0%, 16,33 and with hypertension from 18.3% to 81.3%.…”
Section: Figure 1 Prisma Diagrammentioning
confidence: 99%
“…African American patients are also shown to have a significantly higher readmission score but have a lower mortality score than white patients despite having a longer LOS and total charge. Lee et al noted similar findings of increase LOS and risk of readmission, however, there were no differences in cost or mortality [19]. It is difficult to speculate the reason for a longer LOS despite better outcomes and lower mortality score.…”
Section: Discussionmentioning
confidence: 80%
“…Further, in 1 in 9 deaths, HF is a contributing factor to mortality. Moreover, in one study with adult patients, racial differences were noted among young patients with HF (aged <50 years) [ 6 ]. More specifically, African Americans have a 20 times higher incidence rate of HF compared to that of White Americans [ 2 , 6 ], and among patients aged younger than 75 years, African Americans have the highest incidence of HF and often have an earlier age of HF onset [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in one study with adult patients, racial differences were noted among young patients with HF (aged <50 years) [ 6 ]. More specifically, African Americans have a 20 times higher incidence rate of HF compared to that of White Americans [ 2 , 6 ], and among patients aged younger than 75 years, African Americans have the highest incidence of HF and often have an earlier age of HF onset [ 6 ]. The American Heart Association estimates that by 2030, there will be a 30% increase (from 2012) in the prevalence of HF among African Americans [ 2 ].…”
Section: Introductionmentioning
confidence: 99%